Synthesis of Vanadium Pentoxide (V₂O₅) by Green Method Using Olive Oil as A Reducing Agent and Study of its Physical Properties - Saleh Yaseen, Ahmed; Yosef Othman Homeda; Mohammad M. Al-Tufah; Mutlak Saud Khalaf; Mohannd Faisal Shareef (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study reports the green synthesis of vanadium pentoxide (V₂O₅) using virgin olive oil as a natural and environmentally benign reducing agent. The approach aims to minimize the environmental impacts associated with conventional synthesis routes. Structural and physicochemical characterizations confirmed the successful formation of nanoscale V₂O₅. X‑ray diffraction (XRD) analysis indicated an average crystallite size of approximately 16.57 nm, evidencing high crystallinity. Fourier‑transform infrared spectroscopy (FTIR) revealed characteristic V=O and V–O–V vibrations with bands associated with physisorbed water, confirming the correct oxide framework. Field‑emission scanning electron microscopy (FE‑SEM) showed irregularly shaped nanoparticles with a representative particle diameter of ~32.62 nm. Brunauer–Emmett–Teller (BET) and Barrett–Joyner–Halenda (BJH) analyses yielded a specific surface area of 10.817 m²/g, a total pore volume of 0.024277 cm³/g, and a broad mesoporous distribution (20–90 nm). Energy‑dispersive X‑ray spectroscopy (EDX) confirmed the purity of V₂O₅ with weight fractions of V (69.40%) and O (30.60%), consistent with the stoichiometric composition. Overall, the results demonstrate the effectiveness of olive oil as a green reducing agent for preparing nanoscale V₂O₅, which is promising for catalysis, energy storage, sensors, and clean‑energy applications.